Survival after Laparoscopic versus Abdominal Radical Hysterectomy in Early Cervical Cancer: A Randomized Controlled Trial - Silveira Campos, Luciana (2021)
Previous studies have reported the safety of laparoscopic radical hysterectomy for treatment of early cervical cancer, as option to laparotomy. This study aims to compare overall survival between laparoscopic versus abdominal radical hysterectomy for early cervical cancer. Methods: A single-center randomized controlled trial enrolled 30 patients with clinically staged IA2 cervical cancer and lymphovascular invasion, IB and IIA, who underwent laparoscopic radical hysterectomy (16) or abdominal radical hysterectomy (14). Result: The mean overall survival time was 74.74 months (CI 95%: 54.15-95.33) for LRH 91.67 months (CI 95%: 74.97-108.37) for ARH (logrank test = 0.30). The mean disease-free survival time was 81.07 months (CI 95%: 60.95-101.19) for LRH and 95.82 months (CI 95%: 80.18-111.47) for ARH (log-rank test = 0.371). The overall survival hazard ratio was 2.05 (CI 95%: 0.51-8.24), and the disease-free hazard ratio was 2.13 (CI 95%: 0.39-11.7). Conclusion: Our study suggests a nonsignificant trend of worse outcomes for LRH. In light of recent controversy and need for prospective studies, further studies in different populations are required for definite conclusions and until then, patients should be aware of risks and benefits, survival data and quality of life outcomes related to both surgical techniques.